2020
DOI: 10.1111/ggi.13921
|View full text |Cite
|
Sign up to set email alerts
|

Oral health for achieving longevity

Abstract: Oral frailty is defined as a decrease in oral function accompanied by a decrease in mental and physical functions. Studies showing that people with oral frailty are at high risk of physical frailty, sarcopenia, severe conditions requiring nursing care and death have been reported in Japan. An increase in life expectancy and maintenance of teeth result in a decrease in the effect of the number of teeth. In contrast, a decrease in oral function as a result of aging has been suggested to have major effects on dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
96
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(99 citation statements)
references
References 56 publications
2
96
0
1
Order By: Relevance
“…It was estimated that the 65% almost of who used to live in nursing homes suffered from oral diseases. Moreover, poor oral status is a strong predictor of the onset of adverse health outcomes, including mortality among the community-dwelling elderly [39,40]. The individualization and the assessment of factors associated with such conditions will help in the prevention or minimization of their negative consequences on health.…”
Section: Discussionmentioning
confidence: 99%
“…It was estimated that the 65% almost of who used to live in nursing homes suffered from oral diseases. Moreover, poor oral status is a strong predictor of the onset of adverse health outcomes, including mortality among the community-dwelling elderly [39,40]. The individualization and the assessment of factors associated with such conditions will help in the prevention or minimization of their negative consequences on health.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) has indicated that oral health is one of the behavioral determinants of active aging [3]. Further, some epidemiological studies have reported that declining oral function may be associated with malnutrition in aged individuals [4,5]. In Japan, oral health measures for the aged play a major role in national health promotion policies, such as the establishment of goals related to the oral function of the aged in the national health plan [6].…”
Section: Introductionmentioning
confidence: 99%
“…Many relationships between oral health and diet and nutrition are known to contribute to oral health or oral disease development [8,9]. The most widely explored associations have been the relationships between the development of dental caries (cavities) and dietary intake of simple sugars and carbohydrates [10,11].…”
Section: Introductionmentioning
confidence: 99%